Verification of user interface software: the example of use-related safety requirements and programmable medical devices - Harrison, Michael douglas (2017)
One part of demonstrating that a device is acceptably safe, often required by regulatory standards, is to show that it satisfies a set of requirements known to mitigate hazards. This paper is concerned with how to demonstrate that a user interface software design is compliant with use-related safety requirements. A methodology is presented based on the use of formal methods technologies to provide guidance to developers about addressing three key verification challenges: 1) how to validate a model, and show that it is a faithful representation of the device; 2) how to formalize requirements given in natural language, and demonstrate the benefits of the formalization process; and 3) how to prove requirements of a model using readily available formal verification tools. A model of a commercial device is used throughout the paper to demonstrate the methodology. A representative set of requirements are considered. They are based on US Food and Drug Administration (FDA) draft documentation for programmable medical devices, and on best practice in user interface design illustrated in relevant international standards. The methodology aims to demonstrate how to achieve the FDA's agenda of using formal methods to support the approval process for medical devices.